2017
DOI: 10.1186/s13568-017-0456-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of commercial inactivated yeast derivatives on the survival of probiotic bacterium Lactobacillus rhamnosus HN001 in an acidic environment

Abstract: This study evaluated the influence of three inactivated yeast derivatives (IYDs) used in wine production, namely OptiRed®, OptiWhite® and Noblesse®, on the viability of the probiotic strain Lactobacillus rhamnosus HN001 in an acidic environment. Addition of the IYDs at 3 g/L significantly enhanced the survival of the probiotic bacteria by 2.75–4.05 log cycles after 10-h exposure in a pH 3.0 buffer. Acid stress assay with IYD components obtained after centrifugation and filtration revealed that water-soluble co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Regarding co-culture samples, LGG cell counts were at around 7 log CFU/mL after 6 weeks of storage for both refrigerated and elevated temperatures, qualifying the general guidelines for probiotic beverages. Better viability of LAB was similarly reported in co-culturing S. cerevisiae EC-1118 with L. rhamnosus in an acidic environment [18]. With regards to mono-culture samples, it was interesting to note that LGG cell counts at 30 • C had a sharp reduction at week 1, but then remained relatively stable (Figure 5B).…”
Section: Shelf Life Monitoring Of Fermented Bread Beveragessupporting
confidence: 59%
See 2 more Smart Citations
“…Regarding co-culture samples, LGG cell counts were at around 7 log CFU/mL after 6 weeks of storage for both refrigerated and elevated temperatures, qualifying the general guidelines for probiotic beverages. Better viability of LAB was similarly reported in co-culturing S. cerevisiae EC-1118 with L. rhamnosus in an acidic environment [18]. With regards to mono-culture samples, it was interesting to note that LGG cell counts at 30 • C had a sharp reduction at week 1, but then remained relatively stable (Figure 5B).…”
Section: Shelf Life Monitoring Of Fermented Bread Beveragessupporting
confidence: 59%
“…To mitigate the viability-damaging effects of the environment on probiotic L. rhamnosus strains, various approaches have been investigated, such as cell microencapsulation and co-culturing with other microorganisms. Studies have shown that the viability of certain strains of L. rhamnosus at 30 • C can be enhanced by co-culturing with Saccharomyces cerevisiae [18] or Candida krusei and Yarrowia lipolytica in milk media [18]. In addition, the yeasts may not only contribute to the survival of LAB, but also enrich the flavor property of the end product [5,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The supernatant collected by centrifuging at 10,000 × g at 4 °C for 15 min was ready to be injected to the UFLC system. The mobile phase setting for sugar separation was referred to the study of Toh & Liu (2017). In brief, the mobile solution was an acetonitrile‐water mixture at the ratio of 8:2 (v/v), and the flow rate was 1.4 mL min −1 at 30 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The potential of mixed microbiomes in fermented products has been hypothesized to be part of their benefits, and possibly why single strains of probiotics may be less effective (Ouwehand et al 2018). Several studies showed that yeast could positively interact with probiotic bacteria by enhancing their survival and stimulating their growth (Chan et al 2019;Suharja et al 2014;Toh and Liu 2017). The positive effects of yeast might be attributed to the production of nutrients such as peptides, amino acids, and/or vitamins.…”
Section: Probiotic Microorganismsmentioning
confidence: 99%